Respostas

2013-12-06T16:54:07-02:00
a)F(x)= x² - 4x + 2  
Δ = 16 - 4 . 1 . 2
Δ = 16 - 8
Δ = 8
x = 4 + - √8 / 2
x = 4 + - 2√2 / 2 
                                    x = 2 + √2
                                    x = 2 - √2


b)F(x)= 7x²
Δ = 0 - 4 . 0 . 7
Δ = 0
x = 0 + - √0 / 14
                             x = 0
                             x = 0

c)F(x)= x² - 9x
Δ = 81 - 4 . 0 . 1
Δ = 81
x = 9 + - √81 / 2
x = 9 + - 9 / 2
x = 9 + 9 / 2 
                       x = 9
x = 9 - 9 / 2
                       x = 0

d)F(x)= 3x² - 2x - 5
Δ = 4 - 4 . - 5 . 3
Δ = 4 + 60
Δ = 64
x = 2 + - √64 / 6
x = 2 + - 8 / 6 
x = 2 + 8 / 6 
x = 10 / 6
                        x = 5 / 3
x = 2 - 8 / 6 
x = - 6 / 6
                      x = - 1